2009
DOI: 10.1021/ja9068003
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Platensimycin and Related Natural Products

Abstract: Platensimycin (1) is the flagship member of a new and growing class of antibiotics with promising antibacterial properties against drug resistant bacteria. The total syntheses of platensimycin and its congeners, platensimycins B 1 (7) and B 3 (9), platensic acid (2), methyl platensinoate (3), platensimide A (4), homoplatensimide A (5), and homoplatensimide A methyl ester (6) ( Figure 1) are described. The convergent strategy developed toward these target molecules involved construction of their cage-like core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
111
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(113 citation statements)
references
References 109 publications
(69 reference statements)
2
111
0
Order By: Relevance
“…Nicolaou et al 18,[30][31][32][33] reported several strategies for the total synthesis of platensimycin and related natural products. By using platensimycin/platencin as a starting point, they explored the relationship between structure and function.…”
Section: The Search For Analogs/derivatives Of Platensimycin and Platmentioning
confidence: 99%
“…Nicolaou et al 18,[30][31][32][33] reported several strategies for the total synthesis of platensimycin and related natural products. By using platensimycin/platencin as a starting point, they explored the relationship between structure and function.…”
Section: The Search For Analogs/derivatives Of Platensimycin and Platmentioning
confidence: 99%
“…398 Examples of applications are (±)-2-epi-validamine (Scheme 87), 402 pantocin B, 403,404 and (─)-platensimide A (Scheme 88). 299 An 66 application of this rearrangement in large scale has been reported using DIB. A lower yield was obtained when PIFA/pyridine was used (Scheme 89).…”
Section: Hofmann-type Rearrangementmentioning
confidence: 99%
“…Subsequent Schreiber-Fenton fragmentation [18] would provide alkenes 27, which may be elaborated into advanced intermediate 31 as described by Nicolaou and co-workers. [8] The hypothesis was put into practice as shown in Scheme 9. Oxidation of compound 20 with DIB, as detailed earlier, followed by the addition of 30 % hydrogen peroxide, afforded a 3:2 mixture of unassigned diastereomers of hydroperoxyketal 25 in 64 % overall yield.…”
Section: Scheme 4 the Formation Of Spiroa C H T U N G T R E N N U N mentioning
confidence: 99%
“…[5d] Nicolaou, [8] their co-workers, and us [3c,e] have shown that such reactive agents can be intercepted by allylsilanes. If the internal olefin were to add to the electrophilic carbon in 6, then cationic intermediate 7 would be primed to undergo a pinacol rearrangement to, ultimately, carbonyl compound 8, arguably through a cyclic, chair-like transition state that should permit control of the configuration of the emerging quaternary carbon.…”
mentioning
confidence: 99%